Studies on Homalomeneae (Araceae) of Borneo XIV –A New Rheophytic Species of Homalomena from Sarawak, Malaysian Borneo - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2014)
Homalomena stella P.C.Boyce & S.Y.Wong is described as a new rheophytic species and illustrated from living plants. Based on several shared morphological characteristics the possible affinity of H. stella with Homalomena havilandii Ridl. is highlighted.